UNCOVERING THE CHALLENGES OF ISLAMIC RELIGIOUS EDUCATION FOR MUALLAF SUKU ANAK DALAM (SAD) CHILDREN - S, M Nurzen (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This article will explore the challenges of Islamic religious education for Suku Anak Dalam (SAD) children who are converts or muallaf. We will discuss the problems faced by the Suku Anak Dalam (SAD) converts in obtaining Islamic religious education in the community. This research uses a descriptive qualitative research approach, data collection through in-depth interviews and observations and documentation. Testing data validity with triangulation of sources and methods. The results of this study show that the children of Suku Anak Dalam (SAD) converts face various challenges in obtaining Islamic religious education, namely the problem of cultural barriers and traditions, social problems such as discrimination and marginalization, accessibility to quality Islamic education institutions, learning that is not in accordance with needs or interests, problems of financial resources and financial support, problems of human resources such as teachers and religious leaders who provide role models and problems of low learning motivation. Strengthening the role of teachers, communities and formal, informal and non-formal Islamic education institutions is essential to overcome these challenges.